A Study on Job Design of Nursing Care in Selected Private and Government Medical Health Care - See, Kok Eng (2003)
In nursing care, shift work is defined as work scheduled, either permanently or frequently, outside normal daytime working hours (Peter Knauth). Shift work can be e.g. permanent work at night, permanent work during the evening or work hours can have changing assignment patterns. Each type of shift system has its advantages and disadvantages, and each is associated with differing effects on well-being, health, social life and work performance. The principal characteristics of shift work are its continuity, the alternation of shifts and a special work schedule. Shift work involves alternating or successive teams is said to be continuous when it is kept up 24 hours a day, everyday, including weekends and holidays. This requires a minimum of four teams of workers (three teams working 8-hours shifts and one team resting) and is usually known as 4x8 continuous shift work. A normal shift lasts 8 hours, the same work schedule is maintained for a number of days, and this determines the rhythm of alternation or rotation of the team. Of the numerous different system of work that disrupt the alternating rhythm of waking and sleeping, only industrial shift work has benefited from systematic research. The purpose of this method of organization of work is to maintain continuous production by means of a series of team relaying one another without a break at the place of work. The need for continuity of production may stem from the continuous nature of the technical process involved or from the requirement of a public service.